Hellenorientalia : the Near Eastern presence in the Bronze Age Aegean, ca. 3000-1100 B.C. : interconnections based on the material record and the written evidence : plus orientalia : a catalogue of Egyptian, Mesopotamian, Mitannian, Syro-Palestinian, Cypriot and Asia Minor objects from the Bronze Age Aegean. - Lambrou-Phillipson, C. (Göteborg)
503, 82 s.